Validation of Engine Performance for Tests on Ballast Water Heat Treatment Using Engine Waste Heat - Rajoo Balaji; Omar Yaakob; Kho King Koh; Faizul Amri bin Adnan; Nasrudin bin Ismail; Badruzzaman bin Ahmad; Mohd Arif bin Ismail (International Journal of Marine Engineering Innovation and Research, 2017)
Heat treatment has been considered as a suitable option for treatment of ballast water. Utilising the waste heat from the diesel engine fresh water and exhaust gases would be an economic option. For recovering the heat from the exhaust gases, heat exchangers are required to be placed in their flow path. The sea water coolant after recovering heat from fresh water has to be directed to this heat exchanger for sterilisation. For testing the effectiveness of these heat recoveries on species’ mortalities, a mini-scale system was arranged and tests were carried out. The engine output and other flow rates were maintained to achieve a temperature range of 55 to 80oC. Data was obtained from the sensors and probes fitted at relevant points. The engine performance was monitored with computerised control equipment. Operational data from five test runs were analysed and verified by two approaches. In the first approach, the heat recovered by the water was compared with the heat lost by the exhaust gases and the maximum variation was observed to be 3.4%. In the second approach, the input energies were computed using two different methods using data values of brake power, thermal efficiency, mass flows, calorific value and specific fuel consumption. A maximum variation of -11% was seen for only one test run, while for other tests the variation was between -0.7% to -1.7%. The values obtained from the connected probes and the computed results were thus validated and further tests on species were carried out.